Insurance adjusting: the review of foreign practice. (Journal of Economic Research & Business Administration, 2015)
In the articlethe essence of institute insurance adjustingwhich has received a wide circulation in the western countries with a high level of development of insurance business is considered. Adjuster represents interests of the insurance company in the decision of questions on settlement of the declared claims of the insurant to communications with an insurance case. Adjuster aspires to reach the agreement with the insurant about the sum of the insurance compensation which is a subject payment, proceeding from the obligations of the insurer taken on the prisoner by it to the contract of insurance. In the articleforeign experience of development adjustingactivity on an example of the Russian Federation and a problem characteristic for this sphere is considered. In difference from Russia where adjustingactivity has already was extended and continues to develop in Kazakhstan of adjusterand adjustingactivity does not exist at all, there are no centers of training on a trade adjuster, there is no special adjusters association. Meanwhile, presence in the insurance market of any country of such institute testifies to a high level of development of insurance business. Considering absence in the insurance market of Kazakhstan of a adjuster’s occupation studying of experience of the developed countries is represented very actual.
Keywords: Adjusting; insurance; insuranceloss; appraisal of damage; adjustment of claim